Analytical study on new types of reduced beam section moment connections affecting cyclic behavior. (June 2015) - Rahnavard, R.; Hassanipour, A.; Siahpolo, N.
Highlights: We created eight moment connections with different shape of reducing beam flange using ABAQUS software. We compared the models during cyclic behavior. In the RBS connection with the same holes and varied holes, plastic deformations take place significantly in the beam. Reduced beam section using varied holes, dissipate energy more than other types of reduction and also has minimum magnitude of out of plane buckling. Abstract: Recent earthquakes have shown that steel moment frame (SMF) with weld connections are so brittle. According to the studies conducted, great damages are due to the cracking of the weld between the beam flange and the column face and inducing concentrated stresses in this area. A useful approach to reduce the stress concentration at the panel zone could be the use of reduced beam section (RBS). Given the enormous impact of seismic behavior and ductility of the panel zone, RBS moves plastic hinge formation at an appropriate distance from column face. In this study, eight moment connections with different shape of reducing beam flange have been modeled using ABAQUS computer program and compared with each other during cyclic behavior. The obtained result of this study showed that using varied holes, reduced beam section is more ductile and will dissipate energy more than other connections.